The healthcare architecture of Zoja Dumengjić in the context of Andrija Štampar’s ideology - Matej Knežević (Studia Lexicographica, 2023)
Through his principles, Andrija Štampar established the foundations of public health and social medicine. By implementing his ideas, he changed the paradigm of existing medical opinions, focusing on preventive medicine. As a framework for acting on such medical tendencies, architecture was understood as an area of great importance. Working through the School of Public Health, Štampar established the Department of Healthcare Architecture as a space where the principles of social medicine are intertwined with the concepts of new spatial planning. Architect Zoja Dumenjgić also worked within this department, and her work was strongly based on Andrija Štampar’s social principles. Zoja Dumenjgić is a significant personality of Croatian 20th-century architecture, who left an extensive and significant contribution precisely in the specialised field of healthcare architecture. A brief overview of the diversity and scope of her work and life is presented, based on existing literature. Her portfolio includes projects of various typologies, including medical centers, dispensaries, and large hospital complexes. She made a particularly significant contribution to the architecture of tuberculosis sanatoriums in Croatia. Her most significant architectural accomplishments are additionally highlighted, especially those that reflect the principles of Štampar’s ideology to a significant extent. Her work in the field of healthcare architecture is rooted in modernism and represents an ideal example of how architecture managed to reflect new humanistic values and approach space as an instrument for improving the quality of life and health.